2017
DOI: 10.1159/000477216
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes of Dietary Replacement of Saturated Fatty Acids with Unsaturated Fat Sources in Adults with Overweight and Obesity: A Systematic Review and Meta-Analysis of Randomized Control Trials

Abstract: Background: Obesity and dyslipidemia are frequently treated with dietary interventions before pharmacotherapy is given. Diets high in unsaturated fat have proven advantageous to disease treatment. Aims: The purpose of this systematic review and meta-analysis was to assess the evidence of the effect of saturated fatty acids (SFA) replacement with unsaturated fatty acids (UFA) in metabolically healthy adults with overweight and obesity on markers of dyslipidemia and body composition. Methods: Keyword search was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 42 publications
2
41
0
Order By: Relevance
“…Currently, dietary intakes of EFA (ALA, LA), the FADS enzyme substrates, and LCPUFA are low in the Mexican population [41], and thus carriers of the T-allele of FADS1 -rs174546 may be at an even greater disadvantage if they do not meet dietary recommendations. Furthermore, a meta-analysis for dyslipidemias found that a high intake of unsaturated fat relative to saturated fat reduces TC levels by 10.68 mg/dL, as LCPUFAs serve as key transcription regulators in genes related to de novo lipogenesis [42, 43]. A high intake of unsaturated fat, especially LA, is associated with a decreased risk of CVD and coronary heart events, despite the role of these compounds in pro-inflammatory signaling pathways [44].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, dietary intakes of EFA (ALA, LA), the FADS enzyme substrates, and LCPUFA are low in the Mexican population [41], and thus carriers of the T-allele of FADS1 -rs174546 may be at an even greater disadvantage if they do not meet dietary recommendations. Furthermore, a meta-analysis for dyslipidemias found that a high intake of unsaturated fat relative to saturated fat reduces TC levels by 10.68 mg/dL, as LCPUFAs serve as key transcription regulators in genes related to de novo lipogenesis [42, 43]. A high intake of unsaturated fat, especially LA, is associated with a decreased risk of CVD and coronary heart events, despite the role of these compounds in pro-inflammatory signaling pathways [44].…”
Section: Discussionmentioning
confidence: 99%
“…The promising results of these trials have led to further scientific exploration of differential effects of various types of dietary fatty acids in ameliorating or exacerbating CVD risk. The replacement of saturated for unsaturated fat in the diet has been evidenced to be lipid-lowering and protective against CVD [ 72 , 73 ].…”
Section: Dietary Contributions To Dyslipidemiamentioning
confidence: 99%
“…The mechanisms by which unsaturated fatty acids affect blood lipid profiles have been previously summarized [ 70 , 72 , 74 , 81 ]. In brief, PUFA can serve to upregulate mRNA and thus protein levels of LDL receptors, resulting in increased lipoprotein uptake to the liver [ 82 ].…”
Section: Dietary Contributions To Dyslipidemiamentioning
confidence: 99%
“…More recently, it has been shown that the replacement of saturated fatty acids with monounsaturated fatty acids has a hypocholesterolemic effect while minimizing the decrease in HDL-C concentration. 27 In addition, a diet rich in monounsaturated fatty acids compared with polyunsaturated fatty acids reduces susceptibility to the oxidative modification of plasma LDL-C. 28 The current recommendations suggest that monounsaturated fatty acids intake (such as rapeseed and olive oils) should form 10 to 15% of the total dietary energy intake.…”
Section: Intake Of Monounsaturated Fatty Acidsmentioning
confidence: 99%